Female genital self-mutilation as a cause of vaginal bleeding. Issue 583 (May 1974) - Simpson, M. A.; Anstee, B. H.
Abstract : While self-mutilation in the form of wrist and arm cutting is relatively common and genital self-mutilation in men is well recognized, female genital self-mutilation seems to be strikingly rare. With the exception of injuries secondary to frank self-induced abortion or the insertions of foreign bodies in children, only three cases of female genital self-mutilation have been reported in the literature so far. It is suggested that the phenomenon may not be as rare as hitherto supposed and therefore a further case is reported.